The marbling score assessed with Meat Standards Australia is heritable in Charolais cattle - Matteo Santinello; John Speke Katende; Angela Costa; Nicola Rampado; Jean-François Hocquette; Massimo De Marchi; Mauro Penasa (Italian Journal of Animal Science)
Marbling or visible intramuscular fat is a crucial indicator of beef eating quality. This study investigated the heritability of marbling score (MS), as defined by the Meat Standards Australia (MSA) grading scheme, in Charolais cattle, laying the groundwork for future breeding programs for improving this trait. The dataset included 909 animals (523 young bulls and 386 heifers), progeny of 531 sires and 905 dams imported from France, fattened in specialised units located in northern Italy, and slaughtered in a single abattoir where MS was assessed on a scale from 100 to 1190 using the MSA protocol. Variance components for MS were estimated using a single-trait linear animal model. The heritability (posterior SD) of MS was 0.46 (0.18). The progeny of the top 5% ranked sires (n = 4), with an average estimated breeding value (EBV) accuracy of 0.67, averaged 469 points for MS, compared to 305 points for the progeny of the bottom 5% ranked sires (n = 5). The presence of additive genetic variation for this trait represents a prerequisite for effective selection toward the desired MS to align meat-eating quality with market demands and consumer preferences.